2018
DOI: 10.1111/jfpp.13718
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aqueous ozone on quality and shelf life of shredded green bell pepper ( Capsicum annuum )

Abstract: The effects of aqueous ozone (1–3 mg/L; 1–5 min) treatments on shelf life of capsicum (bell pepper) shreds, some physicochemical characteristics (gas analysis, physiological loss in weight, texture, ascorbic acid, total colour difference and total soluble solids content), microbiological quality and overall acceptability were investigated. After the treatments, the shreds were packed in polypropylene packages and stored under refrigerated conditions (5 ± 0.5°C, 85% ± 5%RH). The analysis of the study indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
6
14
0
Order By: Relevance
“…Ozone was generated from pure oxygen by ozone generator (Li et al, ). Ozone gas was injected in a plastic container (5 L) and gas in excess was moved to destroyer (LDOG‐30, Yancheng Langrun Environmental Protection Technology Co. Ltd, China) through the outlet pipeline (Ummat et al, ). Figure displays the experimental apparatus for aqueous ozone treatments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ozone was generated from pure oxygen by ozone generator (Li et al, ). Ozone gas was injected in a plastic container (5 L) and gas in excess was moved to destroyer (LDOG‐30, Yancheng Langrun Environmental Protection Technology Co. Ltd, China) through the outlet pipeline (Ummat et al, ). Figure displays the experimental apparatus for aqueous ozone treatments.…”
Section: Methodsmentioning
confidence: 99%
“…These results evidence the aqueous ozone treatment is an efficient tactic to improve the edible quality of winter jujube. such as carrot (Souza et al, 2018), black mulberry (Tabakoglu & Karaca, 2018), bell pepper (Ummat, Singh, & Sidhu, 2018), longan (Whangchai, Saengnil, & Uthaibutra, 2006), tomato (Venta et al, 2010), green pepper (Ketteringham, Gausseres, James, & James, 2006), strawberry (Contigiani, Jaramillo-Sánchez, Castro, Gómez, & Alzamora, 2018), and apple (Antos et al, 2018) and equipment sterilization (Zhang, Lu, Yu, & Gao, 2005). Ozone reacts at any times in the water, producing very active monoatomic oxygen which can immediately decompose organic substances and microorganisms.…”
Section: Practical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, 18 sources show negative changes in the color parameter, 11 showed no changes, and 2 showed improvement ( Table 2). Ummat et al [136] showed no immediate effects of ozone on color of shredded green bell pepper; however, ozone-treated samples showed better retention of color for a longer time. Ozone-treated strawberry fruit maintained the best fruit color because of the higher amount of anthocyanins; however, they applied low concentration and short contact time (0.1 ppm for 2 min).…”
Section: Colormentioning
confidence: 98%
“…A number of studies have been conducted to confirm the positive effect of ozone treatment on the shelf life of fruits and vegetables. A few of them were specific to sweet or hot and red or green peppers [12,13,14,15,16]. Most of these studies focus on issues related to the shelf life, like disease development, affecting the microbiological quality; physiological characteristics, resulting in loss of weight, texture, and color; and physicochemical characteristics, concerning ascorbic acid content, physiological and total soluble solids content; or overall acceptability.…”
Section: Introductionmentioning
confidence: 99%